2018
DOI: 10.1177/0361198118790375
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Geodesign for Alternative-Fuel Station Location using “Collablocation” Software

Abstract: Adoption of alternative-fuel vehicles requires a network of conveniently located fuel stations capable of serving the movement patterns of potential users. One hindrance to planning an effective network of stations is the difficulty of integrating the competing views of multiple stakeholders into an agreeable solution. This paper reports on a collaborative geodesign methodology applied to the problem of compressed natural gas fueling locations in the southwestern U.S.A. Geodesign is a multi-stakeholder spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Geo-design combines geography with design and provides tools to support decisionmaking. Geo-design is a holistic approach that has been increasingly applied over the last five years in design, landscaping, transportation, and land-use planning studies [29][30][31]. Nonetheless, to the best of our knowledge, no bicycling studies have applied this approach.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Geo-design combines geography with design and provides tools to support decisionmaking. Geo-design is a holistic approach that has been increasingly applied over the last five years in design, landscaping, transportation, and land-use planning studies [29][30][31]. Nonetheless, to the best of our knowledge, no bicycling studies have applied this approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, to the best of our knowledge, no bicycling studies have applied this approach. For instance, a geo-design approach has been used in designing the fuel station network in the southwestern U.S.; developing an open-sourced platform for facilitating interactive and collaborative development scenarios with spatial data layers and the evaluation of the network performances, named Collablocation [31]. In a similar study, Kazak et al (2019) [32] used a geo-design framework to engage citizens in planning public transport processes to verify the suitability of the planning support systems, such as CommunityViz, to create public transport facilities scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Locating point-based infrastructure facilities on a transportation network contrasts with assigning land uses to polygons, which has been the predominant aim of geodesign studies to date. Kuby et al [65] originally developed Collablocation for a geodesign workshop for locating a network of compressed natural gas (CNG) refueling facilities for long-distance truck travel in the US southwest. In this paper, we adapted the Collablocation platform to the task of locating HRSs at the metropolitan scale in Hartford and included the layers described in Table 3.…”
Section: Collablocationmentioning
confidence: 99%
“…Several studies have reported on the utility to stakeholders of PSS tools [22][23][24]. The other aspect of usefulness, useability, has been evaluated and documented by Afrooz, et al [25], Debnath, Pettit, Leao and Lock [20], and Kuby, et al [26].…”
Section: Introductionmentioning
confidence: 99%